Sistem Informasi Geografis Dalam Pemetaan Kontur Daerah Rawan Banjir Di Desa Laya Kecamatan Baturaja Barat - Azwar, Azwar; destiarini, Destiarini; Sari, Anggun (UNIVED Press, 2023)
Flooding is a relatively high flow of water, and is not accommodated by river channels or canals. The purpose of this study is to analyze flood-prone areas in Laya Village with a spatial-based Geographic Information System (GIS), and identify road sections affected by flooding in Laya Village. with a Spatial-based Geographic Information System (GIS). West Baturaja sub-district has 7 villages and 5 sub-districts and consists of 5 points spread over the area: Batu Putih village, Talang Jawa village, Laya village, Tanjung Agung sub-district, and Batu Kuning sub-district. From the results of the mapping research using the Acrnap GIS software application, it can be mapped in West Baturaja District, obtained data on the number of houses affected by the floods ranging from 150 houses with a flood area of ​​37.73 or a percentage of 47 percent.